A study of effect of physical activity quotient on central obesity (waist hip ratio) in adolescent girls and boys of central India - Gornale, Vinod Kumar; B. Sathenahalli, Veeraraja; Kuber, Manish; Singh, H. P. (International Journal of Contemporary Pediatrics, 2017)
Background: Malnutrition not only refers to undernutrition but also indicates over nutrition in form of obesity. Obesity in childhood, a predisposing factor for obesity in adult hood is on rise. Various factors are like urbanization, technology based sedentary life style, high-fat, high-sugar junk food consumption, increasing purchasing power, lack of exercise, excessive TV viewing are considered responsible for it. Level of physical activity has an implication over obesity. This study has been carried out to identify correlation between obesity and physical activity. The objective of the study was to correlation between physical activity and obesity. Methods: The present study was a prospective, cross sectional, observational, cohort study and was undertaken in private sector secondary school in Rewa. 250 school going girls/boys of 11th and 12th standard selected on random basis. Body mass index and physical activity questionnaire score (PAQs) were recorded. Results: Girls and boys with abnormal WHR indicating obesity were 10% each. Abnormal WHR was found to be significantly associated with saturated fat consumption. A better correlation was found between WHR and physical activity level. Conclusions: More objective testing of physical activity may be undertaken in place of or in conjunction with self-reported assessment. Measurement of WHR should be considered more sensitive indicators of obesity as these are also better correlates of CVD.